Effect of strain, wood substrate and cold treatment on the yield and β-glucan content of Ganoderma lucidum fruiting bodies - Cortina-Escribano, Marta; Pihlava, Juha-Matti; Miina, Jari; Veteli, Pyry; Linnakoski, Riikka; Vanhanen, Henri (MPDI AG, 2020)
Wood residues from forestry industries can be potential raw materials for specialty and edible mushroom production. The aim of this study was to evaluate the suitability of wood residues for the cultivation of Ganoderma lucidum originating from boreal forests. The substrates tested included sawdust and wood chips of Betula spp., Populus tremula, Picea abies, Pinus sylvestris and Larix sp. The suitability of the substrates and the ability of the strains to develop fruiting bodies and produce β-glucan were evaluated. Fruiting body formation was supported by applying two different cold shock treatments to substrate bags. The highest yields were observed with MUS192 strain and Betula spp. and P. tremula wood-based substrates. β-Glucan content in the fruiting bodies was highest with the MUS75 and P. tremula wood-based substrate. Based on these findings, the combination of P. tremula wood residues and the MUS192 strain is proposed to enhance the yieldand β-glucan content of the fruiting bodies. A cold treatment of 5 °C is suggested to induce primordia formation and to increase fruiting probability. This is the first time that strains of G. lucidum originating from boreal forests have been compared and successfully cultivated simulating commercial indoor cultivation.
Keywords: Bioconversion; boreal; circular economy; Ganoderma lucidum; mushroom cultivation; polysaccharides; wood side stream; β-glucan